Infant mortality in India: a statistical study using survival and regression methods based on national family health survey data - Karande, Sanjay; Shinde, Ramkrishna Lahu (International Journal Of Community Medicine And Public Health, 2026)
Background: Although infant mortality in India has declined substantially over the past three decades, large social and regional inequalities persist. This study examines long-term trends in infant mortality and quantifies caste-based differentials in infant survival, with special focus on Uttar Pradesh, Madhya Pradesh, and Maharashtra. Methods: Data from all five rounds of the National Family Health Survey (NFHS-1 to NFHS-5; 1992-2021) were used to assess trends in infant mortality. Survival and regression analyses were conducted using NFHS-5 (2019-21). The study included live births occurring in the five years preceding the survey. Infant survival was examined using Kaplan-Meier estimates and log-rank tests. Binary logistic regression models assessed the association between caste and infant mortality after adjusting for socio-economic, demographic, and healthcare factors, accounting for survey design. Results: At the national level, infant mortality in 2019-21 was higher among Scheduled Tribes (ST) (41.6 per 1,000) and scheduled castes (SC) (40.7 per 1,000) than among non-SC/ST infants (32.8 per 1,000). Survival analysis showed significant caste differences in infant survival (χ²=15.02, p<0.001), with higher hazards concentrated in the early months of life. In unadjusted models, SC infants had significantly higher odds of death (OR=1.26; 95% CI: 1.19-1.33), which remained modest but significant after full adjustment (OR=1.09; 95% CI: 1.01-1.18). ST disadvantage was attenuated after adjustment. Maternal education, household wealth, ≥4 antenatal care visits (OR≈0.65), and institutional delivery were strongly protective. Uttar Pradesh and Madhya Pradesh showed persistently high infant mortality, while Maharashtra exhibited lower overall risk but residual tribal disadvantage. Conclusions: Despite sustained declines in infant mortality, caste and regional inequities remain pronounced in India. Strengthening equitable access to quality maternal and newborn care is essential for further reductions.